Scanning Electron Microscopy (SEM) in the surficial cover analysis of the low fluvial-marine terraces in the southern coast of São Paulo state, Brazil - Souza, André de Oliveira; Perez Filho, Archimedes (Revista Brasileira de Geomorfologia, 2022)
The Ribeira de Iguape estuarine system in Southeastern Brazil has resulted from the complex interactions between allogenic (climate, tectonics, and human interventions) and autogenic geomorphological processes. Early studies have shown that the relationship between sedimentary balances, fluvial discharge, and Holocene climate pulses resulted in the coastline displacement and low fluvial-marine terraces morphogenesis, which are composed of the marine and fluvial sedimentary units. In this perspective, this study aimed to investigate whether the microtextural and morphological records on the quartz grains associated with the different allostratigraphic units (marine and fluvial) correspond to the paleoenvironments identified in previous studies. In this study we have used a combination of analyses (grain-size, microtextural, and absolute dating) applied to the surficial cover sampled from two fluvial-marine terraces located on the right and left banks of the Iguape river channel. The results show correspondences between paleoenvironments and microtextures found on the quartz grains, confirming the statements addressed in previous studies that indicated the coastline was positioned about 9 km inland around 3.5-2.7 ka.